Web-Based VRGIS Property Marketing Information System (VRGIS-PMIS) / Siti Aekbal Salleh … [et al.] - Salleh, Siti Aekbal; Md Sadek, Eran Sadek Said; Wan Mohd, Wan Mohd Naim; Mohamad Ariffin, Imran (Research Innovation Business Unit, 2014)
The emergence of panoramic virtual reality (VR) as visualization tools and acceptance of GIS technology in real estate business have seen to be a major factor of integrating these technologies to increase the marketing efficiency and information dissemination. This study presents the integration of panoramic VR and geoprocessing queries of the design and development of the Web_based GIS residential property Marketing Information system (WGRPMIS). This system intended to be integrated with the virtual GIS technology enabling the consumers to virtually explore the potential property upon the multi criteria selection through assisted geo-processing query. The system is built using ArcGIS Desktop 10, ArcGIS server 10 and ArcGIS Viewer for Flex 3.4. The client-server architecture used for this system is Representational State Transfer (REST) where the client web application is built using Adobe Flex Application programming Interface (API) through application builder, and customized using Widgets and scripting using extensible Markup Language (XML). The spatial data features are stored in a Geodatabase and published as Map Service throughArcGIS server. The base maps are acquired from the online web services (Bing, ESRI) and the Animation/Panoramic view of the property is stored in Adobe Shockwave Flash (SWF) file format. The objectives of this study are to web-enable the existing GIS Residential Property marketing Information system (GRPMIS) for wide range accessibility; to improve the user selection and enhance processing queries for fast response and accurate information retrieval; and to integrate the existing system with panoramic VR that will enhance the user experience and enable virtual exploration. The system provides powerful marketing tools for the users, seller and buyers. It has a huge potential to be commercialized with the current property marketing system available in Malaysia such as www.mudah.my, www.iproperty.com, www.auctionmart.my, www.starproperty.com, www.propertyguru.com. my, www.myproperty.com.my, www.thinkproperty.my, www.adarumah.com and many more. This system offers more flexible way with useful information stated above to make selling and buying a property more enjoyable and fulfilled without neglecting important information. This study highlighted numerous potential of panoramic VR and GIS potential that can be integrated into a system. The potential expansion of the Pilot system (GRPMIS) was successfully improved with the capabilities to perform some GIS elements of analysis (geo-processing) within the improved system (WGPMIS). With minimum cost, the improved system is able to view the GIS data layers online with the availability of BING map and functions are enabled through the use of Representational State Transfer (REST) as client -server architecture. The integration of panoramic VR has been notably simplified the 3D GIS representations by using the image-based panoramic that offers significantly high resolution of visualization. The web application was mainly built using ADOBE Flex Application programming Interface (API) through application builder, and most customization using Widgets and Extensive Mark-up Language (XML) scripting.